The Factors Influencing Intention To Use Mobile Banking Among Generation Y And Z - Sabilla, Anisa Moza; Soma, Abdul Mukti; Sitorus, Palti Marulitua (Universitas Ibn Khladun Bogor, 2024)
Advancements in information technology have accelerated the global expansion of the internet, proceed the financial sector to have a major shift. The mobile banking apps growth is one of the most significant advances that is transforming the business. While these digital services provide several benefits to customers, they are also vulnerable to possible cyber threats. The digital transformation of banking has highlighted various key challenges, including cyberattacks, banking fraud, hacking, phishing, and the significance of security awareness. SEM PLS is used in data analysis, and 400 respondents from Generation Y and Z. Identifying the factores affecting the intention to use mobile banking is the purporse of this study. Therefore, this study found that perceived security, perceived privacy, security awareness, and trust are key factor in influencing the intention to use. Moreover, trust also plays a big role that has significacnt and positive impact on the intention of using mobile banking, with perceived usefulness as a moderator.